2016
DOI: 10.1080/02699931.2015.1127215
|View full text |Cite
|
Sign up to set email alerts
|

A review of cognitive biases in youth depression: attention, interpretation and memory

Abstract: Depression is one of the most common mental health problems in childhood and adolescence. Although data consistently show it is associated with self-reported negative cognitive styles, less is known about the mechanisms underlying this relationship. Cognitive biases in attention, interpretation and memory represent plausible mechanisms and are known to characterise adult depression. We provide the first structured review of studies investigating the nature and causal role of cognitive biases in youth depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 83 publications
6
104
1
1
Order By: Relevance
“…In our model, the route from early trauma to PLEs can be characterized by selected information-processing biases, namely, attention to threat and safety behaviours that contribute to negative beliefs on self-efficacy and coping abilities, which in turn are associated with affective symptoms such as irritability, sadness and fatigue. Association of cognitive biases with depression (eg, Beevers, 2005;Platt, Waters, Schulte-Koerne, Engelmann, & Salemink, 2017) and psychosis spectrum disorders (Moritz et al, 2010;Ramos & Torres, 2016) has already been widely discussed. In our study, we focused in particular on two types of biases: attention to threat and safety behaviours that are important for the development of psychosis (van der Gaag et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In our model, the route from early trauma to PLEs can be characterized by selected information-processing biases, namely, attention to threat and safety behaviours that contribute to negative beliefs on self-efficacy and coping abilities, which in turn are associated with affective symptoms such as irritability, sadness and fatigue. Association of cognitive biases with depression (eg, Beevers, 2005;Platt, Waters, Schulte-Koerne, Engelmann, & Salemink, 2017) and psychosis spectrum disorders (Moritz et al, 2010;Ramos & Torres, 2016) has already been widely discussed. In our study, we focused in particular on two types of biases: attention to threat and safety behaviours that are important for the development of psychosis (van der Gaag et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Both anxiety and depression are associated with negative interpretation biases, which have been demonstrated in adults (for a review, see [2]), and also in adolescents specifically (e.g., [3], [4], [5]). Cognitive Bias Modification of Interpretations (CBM-I) is an experimental paradigm that has potential to be developed into a low-barrier early intervention for anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Developmental studies have reported information processing biases in depression, including increased engagement with negative information and excessively negative interpretations of emotional events (45,46). Our analyses suggest that intersubject synchronization is related to the emotional content of the stimulus.…”
Section: Emotional Movie Content Weakens the Relationship Between Iscmentioning
confidence: 56%